Anemia management in patients on peritoneal dialysis: efficacy and safety of epoetin δ - Bruce S. Spinowitz (Haematologica, 2008)
In a one-year, multicenter, open-label, uncontrolled trial, epoetin δ was given subcutaneously, 1–3-times weekly to peritoneal dialysis patients who had previously received an epoetin. Dose was adjusted to maintain hemoglobin at 10.0–12.0 g/dL. The primary endpoint was mean hemoglobin over weeks 12–24. Safety was assessed. Mean±SD baseline hemoglobin was 11.2±0.9 g/dL. Hemoglobin over weeks 12–24 was 11.6±1.1 g/dL. Adverse events were those expected in this patient population. No life-threatening adverse events occurred. Subcutaneous epoetin δ was effective and well tolerated for the treatment of anemia in peritoneal dialysis patients.